Dynamic Obstacle Avoidance Path Planning of Dual-Manipulator based on APF-RRT - Peng Peng; Zhian Zhang; Xuegong Huang (Jixie chuandong)
Aiming at the defect that the traditional artificial potential field method（APF） is easy to fall into the local minimum in the obstacle avoidance path planning of the 6-DOF dual-manipulator system，an improved APF algorithm combined with an improved rapidly-exploring random trees（RRT） algorithm is proposed for obstacle avoidance path planning. The working space of the dual-manipulator system is analyzed，and the possibility of the interference of the dual-manipulator system is confirmed. For the path planning of the dual-manipulator，the improved APF is used to plan the path of the main manipulator，and it is used as the dynamic obstacle of the slave manipulator to plan the motion path of the slave manipulator. The improved RRT is used to adaptively select the temporary target points to solve the problem of falling into the local minimum when planning the path of the slave manipulator. The improved APF is used to plan the remaining path of the slave manipulator. Simulation analysis shows that the improved APF-RRT algorithm can solve the obstacle avoidance path planning problem of the dual-manipulator system more quickly and accurately than the traditional algorithm.